Not so innocent: Impact of fluorophore chemistry on the in vivo properties of bioconjugates. (August 2021) - Usama, Syed Muhammad; Thapaliya, Ek Raj; Luciano, Michael P.; Schnermann, Martin J.
Abstract: The combination of targeting ligands and fluorescent dyes is a powerful strategy to observe cell types and tissues of interest. Conjugates of peptides, proteins, and, in particular, monoclonal antibodies (mAbs) exhibit excellent tumor targeting in various contexts. This approach has been translated to a clinical setting to provide real-time molecular insights during the surgical resection of solid tumors. A critical element of this approach is the generation of highly fluorescent bioconjugates that maintain the properties of the parent targeting ligand. A number of studies have found that fluorophores can dramatically impact the pharmacokinetic and tumor-targeting properties of the bioconjugates they are meant to only innocently observe. In this review, we summarize several examples of these effects and highlight strategies that have been used to mitigate them. These include the application of site-specific labeling chemistries, modulating label density, and altering the structure of the fluorescent probe itself. In particular, we point out the significant potential of fluorophores with hydrophilic but net-neutral structures. Overall, this review highlights recent progress in refining the in vivo properties of fluorescent bioconjugates, and we hope, will inform future efforts in this area.